2021
DOI: 10.1002/lno.11929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the precariousness of coral recovery when coral and macroalgae are alternative basins of attraction

Abstract: When coral and macroalgae are alternative attractors, the trajectory of the benthic community following a major disturbance is shaped in part by whether herbivores keep macroalgae suppressed, leaving reef surfaces in a state suitable for coral colonization. Because macroalgae tend to colonize much faster than coral, an important issue is how close ambient herbivory is to the level where control of macroalgae is lost, that is, the precariousness of the coral-invasible state relative to the switch-point to macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…With decreased commercial fishing due to COVID‐19, we expect that there will be greater top‐down control this year compared to years when fishing pressures are higher. On the coral reefs of Moorea, seaweeds are controlled by herbivorous fishes (Adam et al, 2011 ) that are targeted by the local small‐scale fishery (Leenhardt et al, 2016 ; Rassweiler et al, 2020 ), and research has shown that intensification of fishing (Holbrook et al, 2016 ) and alteration of fisher behavior (Rassweiler et al, 2021 ) can reduce resilience of the coral state and promote a switch to seaweed dominated reefs that can represent a difficult‐to‐reverse, alternative basin of attraction (Schmitt et al, 2019 , 2021 ). Relaxation of fishing would strengthen resilience of coral communities to other disturbances such as storms and heat waves (Holbrook et al, 2016 ).…”
Section: Effects Of the Anthropause On Ecosystemsmentioning
confidence: 99%
“…With decreased commercial fishing due to COVID‐19, we expect that there will be greater top‐down control this year compared to years when fishing pressures are higher. On the coral reefs of Moorea, seaweeds are controlled by herbivorous fishes (Adam et al, 2011 ) that are targeted by the local small‐scale fishery (Leenhardt et al, 2016 ; Rassweiler et al, 2020 ), and research has shown that intensification of fishing (Holbrook et al, 2016 ) and alteration of fisher behavior (Rassweiler et al, 2021 ) can reduce resilience of the coral state and promote a switch to seaweed dominated reefs that can represent a difficult‐to‐reverse, alternative basin of attraction (Schmitt et al, 2019 , 2021 ). Relaxation of fishing would strengthen resilience of coral communities to other disturbances such as storms and heat waves (Holbrook et al, 2016 ).…”
Section: Effects Of the Anthropause On Ecosystemsmentioning
confidence: 99%
“…These researchers document the threshold density of sea urchins at which shifts occur and the long-term permanence of the algal state after urchin die-off. Benthic communities in Moorea (French Polynesia) are dominated either by coral or macroalgae, with the latter establishing more readily when herbivory drops below thresholds (Schmitt et al 2022). Intriguingly, the fate of fish herbivores on the reefs of Moorea is tied to fisher behavior that selects for low macroalgal sites (Rassweiler et al 2022).…”
Section: Application To Diverse Systemsmentioning
confidence: 99%
“…However, six genera of herbivorous fishes (Naso, Scarus, Siganus, Chlorurus, Acanthurus, Calotomus) together comprise nearly 60% of the abundance and biomass of the catch (Rassweiler et al 2020). These herbivorous fishes are critical to the resilience of the reefs due to their potential to prevent proliferation of macroalgae (Han et al 2016;Schmitt et al 2019Schmitt et al , 2021.…”
Section: Study Sitementioning
confidence: 99%
“…Recent experimental work in Moorea has demonstrated this hysteresis and shown that at least some areas in the lagoons lie within the parameter space where either macroalgae-or coral-dominated states can persist (Schmitt et al 2019(Schmitt et al , 2021. Thus, we focused our remaining model analysis on scenarios in which parameters for fishing and fish dynamics yield alternative outcomes depending on the starting conditions (i.e., coral vs. macroalgal dominance).…”
Section: Dynamics If Fishers Ignore Macroalgaementioning
confidence: 99%
See 1 more Smart Citation